Development and Evaluation of an Open-Source, Online Training for the Measurement of Adult-Child Responsivity at Home and in Early Childhood Education and Care Settings - Rodrigues, Michelle; Schneider, Alessandra; Sokolovic, Nina; Brunsek, Ashley; Oré, Beatriz; Perlman, Michal; Jenkins, Jennifer M. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Efforts to monitor and improve responsive caregiving for young children, because of its importance for child development, are part of the United Nations Sustainable Development Goals. Two brief observational measures of responsive caregiving have been developed and validated (Responsive Interactions for Learning—parent [RIFL-P] and educator [RIFL-Ed] versions), with the RIFL-P available in English, Portuguese, and Spanish. The aim of the current study was to present and evaluate two online training programs for the RIFL measures. These distance learning courses were designed as open-source and asynchronous to enable their use in low- and middle-income countries and remote areas. The following course components are used: readings, lectures, observation of interactions on video, coding practice with automated feedback on item coding, and quizzes. Of the 76 trainees who registered for one of the online courses, 58 (76%) completed all theoretical module components. Student performance was generally high. Marks on quizzes ranged between 83%–100%. Ninety percent of those who took the reliability tests passed (40/44). Student satisfaction during and after the course was high. The effective online training programs are available free of charge and the RIFL suite of measures is efficient to implement. Implications for research and practice are discussed.